Alloy selection for service in chlorine, hydrogen chloride and hydrochloric acid : a guide to the use of nickel-containing alloys - Davies, Michael (Nickel Institute, 2018)
Gaseous chlorine at low temperatures and in the absence of moisture is not particularly corrosive and is commonly handled in carbon steel. If any water is present, however, chlorine becomes aggressive to many metals. Similarly, dry hydrogen chloride (HCl) is not corrosive to most metals. Once it is dissolved in water hydrochloric acid is formed and this is corrosive to many metals and alloys. In this publication, each of these three substances, chlorine, hydrogen chloride and hydrochloric acid is discussed under various conditions. Materials considered include steels, stainless steels, nickel-base alloys, copper-base alloys, titanium, zirconium and tantalum.
Keywords: Alloys -- Corrosion.; elektronické knihy; electronic books